Preparing for The Twenty-First Century - Kennedy, Paul (London Fontana Press, 1993)
Following on from his book "The Rise and Fall of the Great Powers", the author looks at the different ways in which "society" prepares itself for the arrival of the 21st century. Digesting and synthesizing developments in population growth, environmental change, biotechnology, robotics, communications technology and global financial markets, this book looks at the possible future for the developed world.
Includes Bibliography and Index.
Keywords: Twenty-First Century -- Technology--Social Aspects -- World Politics -- Social Change